1994
DOI: 10.1002/ajmg.1320490207
|View full text |Cite
|
Sign up to set email alerts
|

Walker‐Warburg syndrome: Report of three affected sibs

Abstract: Walker-Warburg syndrome (WWS) is a lethal, autosomal recessive disorder characterized by Type II lissencephaly, retinal malformation, cerebellar malformation, and congenital muscular dystrophy. We report on 3 sibs with WWS born to a consanguineous couple. The fetal hydrocephalus associated with this syndrome, while not consistent or necessary for diagnosis, is the key manifestation for its prenatal detection. These sibs illustrate the importance of a careful search for associated malformation(s) in a fetus or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…G.S. Pai kindly submitted autopsy microslides from a reported fetal case [28]. We observed gonadoblastoid testicular dysplasia in the submitted testis slide.…”
Section: Addendummentioning
confidence: 80%
“…G.S. Pai kindly submitted autopsy microslides from a reported fetal case [28]. We observed gonadoblastoid testicular dysplasia in the submitted testis slide.…”
Section: Addendummentioning
confidence: 80%
“…Twenty-seven of the thirty patients in this study were reported to have all of these findings as well as one or more of the following: cerebellar hypoplasia (25), brainstem hypoplasia (21), agenesis of the corpus callosum (22), agenesis of the septum pellucidum (14), interhemispheric fusion (11), and the presence of an encephalocele (7). One family (family 1) has been described in a previous study [Rodgers et al, 1994].…”
Section: Methodsmentioning
confidence: 98%
“…OE is a characteristic manifestation in some MCA syndromes, including Meckel and Walker-Warburg syndromes. In some families, one affected sib with these syndromes had OE, and another one had hydrocephaly [Anderson, 1982;Rodgers et al, 1994]. If so, OE and hydrocephaly may be different manifestations of the same embryonal abnormality.…”
Section: David-o'callaghan Syndrome Vonmentioning
confidence: 99%